Proceedings of the 2018 ACM International Conference on Bioinformatics, Computational Biology, and Health Informatics 2018
DOI: 10.1145/3233547.3233577
|View full text |Cite
|
Sign up to set email alerts
|

DeepAnnotator

Abstract: Genome annotation is the process of labeling DNA sequences of an organism with its biological features, and is one of the fundamental problems in Bioinformatics. Public annotation pipelines such as NCBI integrate a variety of algorithms and homology searches on public and private databases. However, they build on the information of varying consistency and quality, produced over the last two decades. We identified 12,415 errors in NCBI RNA gene annotations, demonstrating the need for improved annotation program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Other approaches that are more directly targeted to genome annotation have been proposed ( Yip et al, 2013 ; Shen et al, 2022 ). A more complete solution for this purpose is presented by DeepAnnotator ( Amin et al, 2018 ), which provides a generalized computational approach for genome annotation at an F-score of 94%. DeepAnnotator is a deep-learning-based tool for functional annotation of proteins.…”
Section: Selected Applications Of Deep Learning In Bioinformaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches that are more directly targeted to genome annotation have been proposed ( Yip et al, 2013 ; Shen et al, 2022 ). A more complete solution for this purpose is presented by DeepAnnotator ( Amin et al, 2018 ), which provides a generalized computational approach for genome annotation at an F-score of 94%. DeepAnnotator is a deep-learning-based tool for functional annotation of proteins.…”
Section: Selected Applications Of Deep Learning In Bioinformaticsmentioning
confidence: 99%
“…Following genome assembly and annotation, another measure is the expression of such genes in an organism, especially the differential expression among different phenotypes. Several studies have shown that deep-learning models provide more accurate predictions of gene expression than traditional methods ( Amin et al, 2018 ; Avsec et al, 2021 ). High-throughput gene expression profiling technologies, such as DNA microarrays and RNA sequencing, provide large gene expression datasets that can be analyzed using deep-learning algorithms ( Zhang et al, 2021 ).…”
Section: Selected Applications Of Deep Learning In Bioinformaticsmentioning
confidence: 99%
“…Sequence-based machine learning models trained on large-scale genomics data capture complex patterns in the sequence and can predict diverse molecular phenotypes with great accuracy. Recently, convolutional neural networks have demonstrated superior performance over other architectures across most sequence-based problems [3, 4, 5, 6, 7, 8, 9, 10, 11], sometimes combined with LSTMs [12, 13, 14, 15] or transformer layers [16, 17].…”
Section: Introductionmentioning
confidence: 99%
“…In the last several years, DL networks have been employed for some elements of gene calling with promising results. DL has been used to predict genes in prokaryotes [Amin et al, 2018]; whether RNAs are coding or non-coding [Hill et al, 2018]; whether human sequences are exons or introns [Singh et al, 2021]; splice site type and strength [Louadi et al, 2019, Zeng and Li, 2022]; and to predict elements of a gene model, such as start codons, splice sites, and poly-adenylation sites [Wei et al, 2021, Liu et al, 2022]. That is, Deep Learning has already shown promising results in tasks related to – or that are a subset of – eukaryotic gene annotation.…”
Section: Introductionmentioning
confidence: 99%